Impacts of molybdate and ferric chloride on biohythane production through two-stage anaerobic digestion of sulfate-rich hydrolyzed tofu processing residue. (July 2022) - Ali, Mahmoud M.; Mustafa, Ahmed M.; Zhang, Ximing; Lin, Hongjian; Zhang, Xin; Abdulbaki Danhassan, Umar; Zhou, Xuefei; Sheng, Kuichuan
Graphical abstract: Highlights: FeCl3 and MoO4 2- addition to TPR increased biohythane yield by 11.9% and 10.5%. 0.6 g/L FeCl3 led to the highest biohythane 797 ml/g-VS and energy 21.8 MJ/kg-VS. Excessive doses of 1.8 and 5.4 g/L FeCl3 inhibited H2 fermentation. Biological SO4 2- reduction was not observed during DF but was detected during MF. SO4 2- reduction raised by 68–104% with the addition of 0.24–1.21 g/L MoO4 2- . Abstract: Biohythane production through one-stage anaerobic digestion of sulfate-rich hydrolyzed tofu processing residue has been hampered by high H2 S production. Herein, two-stage anaerobic digestion was investigated with the addition of molybdate (MoO4 2- ; 0.24–3.63 g/L) and ferric chloride (FeCl3 ; 0.025–5.4 g/L) to the dark fermentation stage (DF) to improve biohythane production. DF supplemented with 1.21 g/L MoO4 2- increased hydrogen yield by 14.6% over the control (68.39 ml/g-VSfed ), while FeCl3 had no effect. Furthermore, the maximum methane yields of methanogenic fermentation were 524.8 and 521.6 ml/g-VSfed with 3.63 g/L MoO4 2- and 0.6 g/L FeCl3 compared to 466.07 ml/g-VSfed of the control. The maximum yields of biohythane and energy were 796.7 ml/g-VSfed and 21.8 MJ/kg-VSfed with 0.6 g/L FeCl3 when the sulfate removal efficiency was 66.7%, and H2 S content was limited at 0.08%. Therefore, adding 0.6 g/L FeCl3 is the most beneficial in improving energy recovery and sulfate removal with low H2 S content.